Implementasi App.JelajahIlmu.com dalam Penyusunan Modul Ajar Bahasa Inggris Fase E - Takbir Rianto; Kuswahyuningsih; Ika Sulistyawati; Lutfah Iin Setyorini; Siti Fatkhurohmah; Eko Budi Utomo (JURNAL ILMIAH RESEARCH STUDENT, 2025)
This study aims to describe the implementation of App.JelajahIlmu.com in the development of Phase E English Teaching Modules at State Senior High Schools in Central Java and to identify the obstacles in the use of App.JelajahIlmu.com for the development of teaching modules. This study uses a qualitative method with descriptive qualitative techniques. Data analysis was obtained through a systematic process of data collection and organization, with data sourced from observations, interviews, and document reviews, including data collection, data reduction, data presentation, drawing conclusions, and verification. The research findings indicate that 1) the implementation of App.JelajahIlmu.com The implementation process begins with preparation and planning, which includes determining students' learning needs and objectives to design appropriate teaching modules. Teachers use the Jelajah Ilmu application during the design phase to create engaging teaching modules. Additionally, digital content development was carried out by uploading instructional modules and creating evaluation questions that could be automatically graded, enhancing the effectiveness of assessment. The application allows learning to be conducted both online and offline, enabling better interaction between teachers and students and facilitating real-time monitoring of student progress. The implementation results showed positive effects, such as increased student engagement and improved assessment efficiency. Therefore, the Jelajah Ilmu application has proven successful in improving the productivity and quality of English language learning.; 2) However, several challenges were identified, namely a) Limited internet access, b) Human resource constraints. The conclusion of this study is that App.Jelajahilmu.com can be applied in the process of developing teaching modules.